Large Time Behavior on the Linear Self-Interacting Diffusion Driven by Sub-Fractional Brownian Motion With Hurst Index Large Than 0.5 I: Self-Repelling Case - Gao, Han; Guo, Rui; Jin, Yang; Yan, Litan (Frontiers in Physics, 2022)
Let S^H be a sub-fractional Brownian motion with index 12